Potensi ekologis dan pola sebaran teripang Holothuria scabra dan Holothuria vagabunda di Perairan Tanjungkeramat Desa Pangkil, Kabupaten Bintan, Indonesia - Rani Marni; Febrianti Lestari; Susiana Susiana (Akuatikisle: Jurnal Akuakultur, Pesisir dan Pulau-Pulau Kecil, 2020)
The aim of the study was to determine the ecological potential and pattern of the distribution of sea cucumbers in the waters of Tanjungkeramat, Pangkil Village, Teluk Bintan District, Bintan regency. This study uses a survey method, determining the area with a swap area method of 4 areas, measuring the area using a meter with a length and width of 100 x 50 m. The results of the study found 2 types. Sea cucumber from the subfamily namely Holothuriidae and Stichopodidae. The highest density of Holothuroidea species in area I is 46 individual/ha. The lowest density is in area IV which is 12 individual/ha. Sea cucumber density in Tanjungkeramat is still relatively good. The water conditions in Tanjungkeramat still meet the quality standards that support the life of sea cucumber. Distribution pattern in area I with Id value 0.69, area II with Id value 0.68, and area III with a value of 0.42 has an even distribution pattern, while the distribution pattern in area IV Id 1.00 has a random distribution pattern.